2018
DOI: 10.1098/rsos.181462
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive two-dimensional MoS 2 gas sensor decorated with Pt nanoparticles

Abstract: A two-dimensional molybdenum disulfide (MoS2)-based gas sensor was decorated with Pt nanoparticles (NPs) for high sensitivity and low limit of detection (LOD) for specific gases (NH3 and H2S). The two-dimensional MoS2 film was grown at 400°C using metal organic gas vapour deposition. To fabricate the MoS2 gas sensor, an interdigitated Au/Ti electrode was deposited using the electron beam (e-beam) evaporation method with a stencil mask. The MoS2 gas sensor without metal decoration sensitively detects NH3 and H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…Park et al prepared a MoS 2 gas sensor modified with Pt nanoparticles with a low detection limit and high sensitivity for H 2 S gas. The Pt-MoS 2 -based sensor reduced the minimum detection concentration of H 2 S gas to 5 ppm, which was much lower than that of the pure MoS 2 sensor (30 ppm) (Park et al, 2018). The Pt-MoS 2 film structures were formed by the introduction of Pt nanoparticles with ultra-small diameters, which could distinctly improve the performance of sensors.…”
Section: Experimental Analysis About Mos 2 -Based Sensorsmentioning
confidence: 93%
“…Park et al prepared a MoS 2 gas sensor modified with Pt nanoparticles with a low detection limit and high sensitivity for H 2 S gas. The Pt-MoS 2 -based sensor reduced the minimum detection concentration of H 2 S gas to 5 ppm, which was much lower than that of the pure MoS 2 sensor (30 ppm) (Park et al, 2018). The Pt-MoS 2 film structures were formed by the introduction of Pt nanoparticles with ultra-small diameters, which could distinctly improve the performance of sensors.…”
Section: Experimental Analysis About Mos 2 -Based Sensorsmentioning
confidence: 93%
“…For instance, the sensors made of pure MoS 2 showed little response towards different gases but were not able to display full recovery and good selectivity [106]. Park et al [107] reported enhanced NH 3 and H 2 S detection using Pt NPs decorated on MoS 2 -synthesized via vapor deposition technique. Their sensor revealed relatively better performance than that of pure MoS 2 sensors but still did not achieve full recovery to the baseline (see Figure 7A).…”
Section: Experimental Progress In Carbon Materials 2d Tmdcs and Mox-based Chemical Sensorsmentioning
confidence: 99%
“…More specifically, 2D materials (TMDs, BP, silicene, MXene, etc.) are adopted as promising candidates for high-sensitive gas sensors because of the large surface-to-volume ratio and tunable functionality of the surface through decorating transition metals or functional groups [65][66][67][68][69]. The excellent mechanical properties and piezoelectric properties in 2D materials also implicate the applications of sound detectors [70][71][72].…”
Section: Conclusion and Perspectives: 2d Materials In Designing Neurmentioning
confidence: 99%